Proposta para estudo da usinabilidade do aço SAE 8640 com a utilização de insertos quadrados de metal duro e adição de fluidos de corte de origem vegetal - Berkembrock, Gabriel Amon Krindges (2021)
Machining is a highly used process in the mechanical metal industry, for greater productivity it is necessary to increase speed, which generates an increase in temperature, causing mechanical failures, shortening of the useful life and an inadequate surface finish. To solve these problems, an alternative is the use of cutting fluids, which assist in cooling and lubrication, in addition to performing a chip removal function from the cutting zone, improving the surface finish of the part. Currently, most of the cutting fluids used are of mineral origin, harmful and highly toxic to the environment and human health. Thinking about the sustainable issue, the idea of this work is to look for a viable alternative for a “cleaner” manufacturing. With this, a theoretical basis was gathered through the literature and a practical experiment was proposed to obtain final results, in order to replace the use of cutting fluids of fossil origin, for fluids of vegetable origin in the machining of SAE 8640 steel, with a square metal insert hard.